Original articlePrimary angiitis of the central nervous system: a study of histopathological patterns and review of the literature - Suri, Vaishali; Kakkar, Aanchal; Sharma, Mehar C.; Padma, Madakasira V.; Garg, Ajay; Sarkar, Chitra (Folia Neuropathologica, 2014)
Primary angiitis of the central nervous system (PACNS) is a rare form of vasculitis of unknown aetiology. Multifaceted clinical manifestations, non-specific MRI findings, a broad range of differential diagnoses and diverse pathological appearances prove to be a diagnostic challenge. However, a prompt diagnosis and aggressive treatment are crucial to avoid permanent damage. Hence, we present the clinico-pathological spectrum of this entity and highlight the limitations of currently available diagnostic modalities. We describe in detail the histopathological findings of eight cases of PACNS diagnosed at the Department of Pathology, AIIMS, over a period of eight years. Eight cases of PACNS were identified during this period. Five cases (62.5%) showed features of granulomatous vasculitis, two (25%) showed lymphocytic vasculitis and one case (12.5%) showed a predominantly necrotizing pattern of vasculitis. Diagnosis of PACNS is a challenge and requires a high index of clinical suspicion. Appropriate work-up to exclude other conditions is mandatory. Brain biopsy is useful in making the diagnosis and ruling out mimicking conditions.